Contribution of miRNAs in the Pathogenesis of Breast Cancer - Ghafouri-Fard, Soudeh; Khanbabapour Sasi, Ali; Abak, Atefe; Shoorei, Hamed; Khoshkar, Ali; Taheri, Mohammad (Frontiers in Oncology, 2021)
Breast cancer is the most frequently diagnosed cancer among females. Gene expression profiling methods have shown deregulation of several genes in breast cancer samples and have confirmed the heterogeneous nature of breast cancer at genomic level. microRNAs (miRNAs) are among recently appreciated contributors in the breast carcinogenic processes. These small-sized transcripts have been shown to partake in breast carcinogenesis through modulation of apoptosis, autophagy and epithelial-mesenchymal transition (EMT). Moreover, they can confer resistance to chemotherapy. Based on contribution of miRNAs in almost all fundamental aspects of breast carcinogenesis, therapeutic intervention with their expression might affect course of this disorder. Moreover, the presence of miRNAs in peripheral blood of patients potentiates these transcripts as tools for non-invasive diagnosis of breast cancer.